Applications of lasers in dermatology: From hair removal to skin rejuvenation - Hassan Alsobh Morjan (E3S Web of Conferences)
This paper covers some of the uses in dermatology, for both cosmetic and therapeutic applications. It surveys laser technologies used in a series of common procedures in dermatology: hair removal, skin rejuvenation, acne, etc. The review highlights the mechanisms of laser interaction with skin tissue, safety concerns, efficacy, and recent developments in laser technologies. The goal is to facilitate a balanced and broad overview of laser therapies in contemporary dermatology, including who, what, and where they are used, advantages, potential hazards, along with future ramifications.